The discovery of novel immunomodulatory medicinal plants by combination of historical text reviews and immunological screening assays. (5th October 2022) - Ulriksen, Emilie Steinbakk; Butt, Hussain Shakeel; Ohrvik, Ane; Blakeney, Rebecca Angelica; Kool, Anneleen; Wangensteen, Helle; Inngjerdingen, Marit; Inngjerdingen, Kari Tvete
Abstract: Ethnopharmacological relevance: With the advent of immunotherapies against cancers, autoimmune diseases and infections, there is a steady demand for novel medicines. New sources for discovery of potentially novel immunomodulatory compounds are therefore needed. Nature contains a large and diverse reservoir of novel compounds that can be exploited for their potential as new drugs, and exploring the pharmaceutical potential of medicinal plants used in traditional medicine is highly relevant. Aim of the study: We aimed with this study to explore usage of medicinal plants in Scandinavian folk medicine against diseases interpreted to involve the immune system, and to further screen water extracts from previously overlooked medicinal plants in order to discover potential new sources of immunomodulatory compounds. Materials and methods: We systematically investigated historical records dating back to the 1800s with an emphasis on plants used as treatment for wounds or diseases interpreted to be inflammatory. Of 74 candidate plants, 23 pharmacologically under-studied species were selected for further characterization. The plants were collected from their natural habitats in Southern Norway, air-dried, and subjected to boiling water and accelerated solvent extraction. The crude extracts were separated into polysaccharide-enriched fractions and C-18 solid phase extracted fractions. Immunological screenings were performed with all extracts and fractions. Monosaccharide composition and total phenolic content were determined and compared across all species. Results: We identified 10 species with clear immune activating effects and 8 species with immune inhibitory effects by comparing cytokine production by human peripheral blood mononuclear cells, primary human T- and NK-cell proliferation, and nitric oxide production from macrophages. Conclusions: With this study, we provide a comprehensive overview of Scandinavian medicinal plants and their usage, and our findings support an approach of combining historical sources with modern pharmacology in the discovery of plant sources containing potentially new pharmacological compounds. Graphical abstract: Image 1 Highlights: From historical sources on Scandinavian medicinal plants, we selected 23 plants with usage against immune-related ailments. We found immune activating or inhibitory activities within water extracts of the majority of the short-listed plant extracts. Plants with high immune inhibitory activity were predominantly documented in the sources as wound-healing remedies. Plants with primarily immune-activating activities shared usage against the cold or upper airway infections. Success in combining historical sources with modern pharmacology in the discovery of plant sources for possible novel drugs.